2003
DOI: 10.1111/j.1151-2916.2003.tb03360.x
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of TiN/Si3N4 Ceramics by Spark Plasma Sintering of Si3N4 Particles Coated with Nanosized TiN Prepared by Controlled Hydrolysis of Ti(O‐i‐C3H7)4

Abstract: TiN‐coated Si3N4 particles were prepared by depositing TiO2 on the Si3N4 surfaces from Ti(O‐i‐C3H7)4 solution, the TiO2 being formed by controlled hydrolysis, then subsequently nitrided with NH3 gas. A homogeneous TiO2 coating was achieved by heating a Si3N4 suspension containing 1.0 vol% H2O with the precursor at 40°C. Nitridation successfully produced Si3N4 particles coated with 10–20 nm TiN particles. Spark plasma sintering of these TiN/Si3N4 particles at 1600°C yielded composite ceramics with a relative de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…The present authors have reported that TiN/Si 3 N 4 based nanocomposites with excellent mechanical properties and conductivity can be processed through a chemical route and sintered by SPS [10,11]. However, due to the complexity * Corresponding author.…”
Section: Introductionmentioning
confidence: 98%
“…The present authors have reported that TiN/Si 3 N 4 based nanocomposites with excellent mechanical properties and conductivity can be processed through a chemical route and sintered by SPS [10,11]. However, due to the complexity * Corresponding author.…”
Section: Introductionmentioning
confidence: 98%
“…conductive composites, this can facilitate machining of these composites into complex shapes by the more economical electrical discharge machining (EDM). 4 Various Si 3 N 4 composites with addition of an electroconductive secondary phase, such as TiN, 3 TiB 2 , 5 TaN, 6,7 TiC 8 and MoSi 2 , 9,10 have been studied. Among them, Si 3 N 4 -MoSi 2 composites are of special interest.…”
Section: Introductionmentioning
confidence: 99%
“…That is why the TiN content is usually limited to 25-40 vol% (37-52 mass%), i.e., amount necessary to form TiN continuous conductive three-dimensional network and improve toughness and room-temperature strength characteristics without significant decrease in oxidation resistance. [1][2][3][4][5][6][7][8][9][10][11][12] Methods used in the preparation of Si 3 N 4 -TiN composite materials are mainly based on using mechanical mixtures of initial components. These methods cannot provide a homogeneous distribution of titanium nitride in the silicon nitride matrix, a necessary condition of the continuous three-dimensional TiN network in the Si 3 N 4 , as well as sufficient electric conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…13 The hot pressing (HP), pressureless sintering and gaspressure sintering in a nitrogen atmosphere are usual methods for the Si 3 N 4 -TiN ceramic consolidation. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] These methods generally provide high density; however, require the temperatures of 1750 C to 1800 C which result in the formation of coarse-grained structure. 2-6 9-12 Avoiding a high-temperature processing stage, i.e., achieving a finegrain microstructure may lead to enhancement of the functional properties.…”
Section: Introductionmentioning
confidence: 99%